2021
DOI: 10.3389/fpsyg.2021.695354
|View full text |Cite
|
Sign up to set email alerts
|

A Latent Class Analysis of Forensic Psychiatric Patients in Relation to Risk and Protective Factors

Abstract: Forensic psychiatric patients form a very heterogeneous population regarding psychopathology, criminal history, and risk factors for reoffending. Therefore, the present study aimed to investigate whether there are more homogeneous classes of forensic patients based on DSM-IV-TR Axis I and II diagnoses and previously committed offenses, by means of explorative latent class analysis (LCA). It was also investigated which risk and protective factors are significantly more prevalent in one class compared to other c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 50 publications
2
9
0
1
Order By: Relevance
“…In Wallonia psychotic diagnoses were found more frequently and in Flanders this was the case for personality disorders (33). Multiple diagnoses were actually found, and a high number of substance misuse disorders were part of the current study, which is in line with other research (10,33).…”
Section: Discussion Descriptive Analyses Of Patient Profilessupporting
confidence: 93%
See 1 more Smart Citation
“…In Wallonia psychotic diagnoses were found more frequently and in Flanders this was the case for personality disorders (33). Multiple diagnoses were actually found, and a high number of substance misuse disorders were part of the current study, which is in line with other research (10,33).…”
Section: Discussion Descriptive Analyses Of Patient Profilessupporting
confidence: 93%
“…In Italy, a diagnosis of personality disorder was negatively associated with admission to a high security forensic unit ( 3 ). In contrast personality disorders and substance use disorders were frequently found in Dutch high security populations ( 10 ). Treatment length was variable: the median hospital stay in high security institutions in England and Wales was 6.9 years ( 5 ), and in Norway, it was <1 year ( 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to note, however, that a post-hoc ANOVA analysis showed that at the moment of juridical assessment (T1) and after the first 12 months of the stay in the FPCs (T2), psychotic patients scored significantly higher on the clinical scale, and the risk subscale, and significantly lower on the protective skills subscale than non-psychotic patients. This is consistent with evidence that individuals with a psychotic diagnosis are at higher risk for violence and criminal behavior than those without this diagnosis ( 17 , 22 , 31 ). That said, significant differences in trajectories of the clinical scale, and the risk and protective subscales in the first phase of the stay may be attributed to the differences in the initial levels of the risk and protective factors between psychotic and non-psychotic patients.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, we did not find significant differences between cluster B and non-cluster B PDs patients in the trajectories of the clinical scale, and the protective skills subscale. It could be speculated that differences were only found for the risk factors as they are more pronounced in patients with cluster B PDs ( 17 , 23 , 42 44 ) than the lack of protective factors ( 17 , 68 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation